Mandalas de movimentos emergentes na educação do campo em áreas de assentamento do MST na região sul do Brasil - Perin, Angelita Tatiane Silva dos Santos (2023)
This doctoral thesis in Education, developed along the line of Research (LP2) educational public policies, educational practices and their interfaces of the Postgraduate PrograminEducation, at the Federal University of Santa Maria, and within the scope of studiesof theGestar Research Group /CNPq/UFSM, addresses the topic of Rural EducationinMSTsettlement areas. Its general objective is to understand the main emerging movementsinRural Education in MST settlement areas in the Southern Region of Brazil. Andfor specificobjectives it prioritizes: i) recognizing the historical, political and social aspects that constituteRural Education in Brazil; ii) identify emerging contexts in the history of Rural EducationinBrazil; and iii) analyze the tensions and challenges that emerge in schools locatedinMSTsettlement areas in the Southern Region of Brazil. It is based on qualitative researchfromtheperspective of historical-dialectical materialism, carried out with collaborating educatorsfromschools located in MST settlements in the southern region of Brazil, using thestateofknowledge, document analysis, and the mixed online questionnaire and Dialogical Circlesfrom a Freirean perspective for data construction and analysis. The following categoriesofanalysis were listed: totality; contradiction; class struggle; hegemony; mediation; work;historicity; new hegemony; praxis; awareness. As results, we highlight the understandingthatRural Education constitutes an example of a complex historical transition of forces, asit wasforged within a mass social movement, the MST; which represents one of the antagonisticpoles in the correlation of forces in current capitalist society; the difficulty of Rural Educationbeing understood and accepted in the national educational scenario as a teachingmodalityby education systems (municipal and state); while in public schools in settlement areasintheSouth Region, the reality is different, emerging among other situations: active resistancetothe impositions of educational systems, through the valorization of local, social andcultural knowledge and experiences; the resumption, improvement and deepening of thepolitical-pedagogical proposals of school units, aiming at the development of significant teachingandlearning processes that provide opportunities for the construction of knowledge bystudentsand effective learning; the ongoing training of male and female educators in ameaningful and necessary way for a pedagogical practice that is consistent and coherent withtherealityexperienced in everyday school life. It concludes by defending the thesis that intheMSTSettlement areas the movements that emerge in Rural Education are related to theland, thegeneration of dignified, quality and equitable life, with education as a guide and enhancerofemancipatory human formation, with a view to social transformation.